PENGARUH KREDIBILITAS KONTEN TIKTOKROBBYYULIENDRA (ROBBYYULIENDRA) TERHADAP KEBUTUHAN INFORMASI FOLLOWERS - Noval, Novallano; Cindo, Ageng Rara Cindoswari, S.P., M.Si. (SCIENTIA JOURNAL, 2024)
The development of social media today, makes changes in behavior patterns in individuals. One of these social media is the Tiktok application. This now favored by various groups ranging from adults, teenagers to children. With this application, content creators can express themselves through educational, funny and unique videos. The research method used is a quantitative method. The theory used is the theory of media dependency. This study aims to determine the impact of the Tiktok application on the behavior of TikTok followers @robbyyuliedera. The data collection uses a questionnaire. while for data analysis using three flow of activities namely data collection, data reduction, data presentation, and drawing conclusions One of the new forms of communication offered in the world of the internet is social media. Where by using social media on the internet, users can multiply words or things that they experience. The sample was obtained based on the population of followers of the Tik Tok account @robbyyuliendra as of August 10, 2022. This research is to explain the variables identified through technical analysis. Correlation analysis is used to measure the relationship between two variables, the basic idea of correlation analysis is to report the relationship between two variablesKeywords: Education About Missing Information on Followers.